Active Poly(4‐chloromethyl styrene)‐Functionalized Multiwalled Carbon Nanotubes. Issue 16 (15th May 2013) - Chen, Xianhong; Zhou, Mi; Hou, Qinglin; Tu, Xi; Wu, Xiaoli
Abstract Concentrated nitric acid‐treated multiwalled carbon nanotubes (MWCNTs) are functionalized with active poly(4‐chloromethyl styrene) (PCMS) through the esterification reaction of the carboxyl groups of the former and the p‐benzyl chloride groups of the latter in the presence of a phase‐transfer catalyst. Characterization using Raman spectroscopy, Fourier transform infrared spectroscopy, and hydrogen nuclear magnetic resonance spectroscopy demonstrates that the active PCMS chains are chemically tethered onto the side walls (or surfaces) of the MWCNTs. The core‐shell nanostructure of active PCMS‐modified MWCNTs (MWCNT‐PCMS) can be observed by high resolution transmission electron microscopy, and the amount of PCMS present is 31.3 wt% by thermogravimetric analysis. Solubility testing shows that MWCNT‐PCMS dissolves well in tetrahydrofuran, chloroform, toluene, and N, N‐dimethylformamide, and the maximum nanotube concentration in toluene is 413 mg L−1.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>